Alternative Accounting Methods, Information Asymmetry and Liquidity: Theory and Evidence. - Bartov, Eli; Bodnar, Gordon M. (The Accounting Review, 1996)
Studies the information asymmetry perspective of corporate accounting choice. Effects of information asymmetry to transaction costs and liquidity for trading shares; Disclosure opportunity to decrease information asymmetry; Information asymmetry in the choice of functional currency by multinational firms.